The effect of customer trust and commitment on customer sustainable purchasing in e-marketplace, the antecedents of customer learning value and customer purchasing value - Hongsuchon, Tanaporn; Alfawaz, Khaled Mofawiz; Hariguna, Taqwa; Alsulami, Othman Atti (Frontiers in Environmental Science, 2022)
The e-marketplace is a platform used by vendors to conduct transactions and shopping. The success of implementing an e-marketplace depends on customers’ sustainable purchasing. This study integrates customer learning (formative construct) and purchasing (reflective construct) values to measure the level of customer trust and commitment in the e-marketplace to examine their effects on sustainable customer purchases. A total of 428 valid respondents were processed using SmartPLS 3. The results show that the six proposed hypotheses have positive values and significant effects. Customer learning and purchasing values have positive values and significant effects on customer trust and loyalty and have indirect positive values and significant effects on sustainable customer purchases. In other words, customer trust and loyalty have positive values and significant effects on sustainable customer purchases. Thus, the findings of this study have implications for other researchers and practitioners conducting studies on e-marketplaces.